Mental health concerns among collegiate athletes decreased: a prospective analysis during COVID-19 - Slavin, L. E.; Petrie, T. A.; Moore, E. W. G. (Journal of Clinical Sport Psychology, 2025)
During the onset of the COVID-19 pandemic, collegiate athletes endured many general life stressors, lost access to sport-specific resources, had their sport seasons canceled, and suffered disruptions to their athletic identities. Collegiate athletes reported elevated mental health concerns in Spring 2020; however, less is known about how such concerns evolved as the pandemic progressed. Thus, we examined changes in collegiate athletes` mental health status from April/May 2020 (T1) to August/September 2020 (T2). The rate of collegiate athletes` (N = 1,829) mental health concerns decreased significantly across this transitional phase of the pandemic; however, prevalence rates of depression and psychological distress remained high at T2. More women athletes experienced these elevated levels of concern. These results support the need for continued monitoring of athletes` mental health and will inform sports medicine and sport psychology professionals regarding athletes` evolving mental health care needs during times of crisis and transition.